Critical role of inflammatory mast cell in fibrosis: Potential therapeutic effect of IL‐37. (30th July 2018) - Conti, P.; Caraffa, Al.; Mastrangelo, F.; Tettamanti, L.; Ronconi, G.; Frydas, I.; Kritas, S. K.; Theoharides, T. C.
Abstract: Background: Fibrosis involves the activation of inflammatory cells, leading to a decrease in physiological function of the affected organ or tissue. Aims: To update and synthesize relevant information concerning fibrosis into a new hypothesis to explain the pathogenesis of fibrosis and propose potential novel therapeutic approaches. Materials and Methods: Literature was reviewed and relevant information is discussed in the context of the pathogenesis of fibrosis. Results: A number of cytokines and their mRNA are involved in the circulatory system and in organs of patients with fibrotic tissues. The profibrotic cytokines are generated by several activated immune cells, including fibroblasts and mast cells (MCs), which are important for tissue inflammatory responses to different types of injury. MC‐derived TNF, IL‐1, and IL‐33 contribute crucially to the initiation of a cascade of the host defence mechanism(s), leading to the fibrosis process. Inhibition of TNF and inflammatory cytokines may slow the progression of fibrosis and improve the pathological status of the affected subject. IL‐37 is generated by various types of immune cells and is an IL‐1 family member protein. IL‐37 is not a receptor antagonist; it binds IL‐18 receptor alpha (IL‐18Rα) and delivers the inhibitory signal by using TIR8. It has been shown that IL‐37 can be protective in inflammation and injury, and inhibits both innate and adaptive immunity. Discussion: IL‐37 may be useful for suppression of inflammatory diseases induced by inhibiting MyD88‐dependent TLR signalling. In addition, IL‐37 downregulates NF‐κB induced by TLR2 or TLR4 through a mechanism dependent on IL‐18Rα. Conclusion: This review summarizes current knowledge on the role of MC in inflammation and tissue/organ fibrosis, with a focus on the therapeutic potential of IL‐37‐targeting cytokines.